Collaboration Issues In The Uninhabitable House Repair Assistance Program In Banten Province - Alam Muhana Nabil; Herijanto Bekti; Elisa Susanti (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This article discusses the collaborative governance process that occurs in the uninhabitable house assistance program for the poor in banten province. The problem that arises in this research is that the collaboration that runs from the actors is still not running optimally. This is characterized by a lack of face-to-face dialogue, decision-making dominated by the Regional Government, and low mutual trust between actors. This article uses qualitative research methods to explain the process of collaboration in the uninhabitable house assistance program in Banten Province. There are findings in this study that several acts of corruption cases committed by local governments or business entities are the main point of low trust between actors. Another finding is the lack of face-to-face dialogue to discuss decision-making that will be carried out in this program. In addition, community involvement that is only a formality fulfillment makes this program often mistargeted. There is a rejection of housing assistance from the indigenous people of the Baduy tribe because they feel that the houses provided by this assistance are not in accordance with the local wisdom of the Baduy community. Based on the research that has been conducted, this program has achieved several short-term targets, but in its implementation there are still several collaboration processes that have not been able to run well.